2017
DOI: 10.1103/physreva.96.033403
|View full text |Cite
|
Sign up to set email alerts
|

Robust two-level system control by a detuned and chirped laser pulse

Abstract: We propose and demonstrate a robust control scheme by ultrafast nonadiabatic chirped laser pulse, designed for targeting coherent superpositions of two-level systems. Robustness against power fluctuation is proved by our numerical study and a proof-of-principle experiment performed with femtosecond laser interaction on cold atoms. They exhibit for the final driven dynamics a cusp on the Bloch sphere, corresponding to a zero curvature of fidelity. This solution is particularly simple and thus applicable to a wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…The population transfer by an adiabatic passage is an important and prominent approach in quantum control [1][2][3][4]. Frequency-chirped laser [5][6][7], Landau-Zener technique [8][9][10], and a hosseini@sutech.ac.ir Stimulated Raman Adiabatic Passage (SRIRAP) [11][12][13][14][15][16][17] are some of the important methods of the adiabatic population transfer of the quantum systems.…”
Section: Introductionmentioning
confidence: 99%
“…The population transfer by an adiabatic passage is an important and prominent approach in quantum control [1][2][3][4]. Frequency-chirped laser [5][6][7], Landau-Zener technique [8][9][10], and a hosseini@sutech.ac.ir Stimulated Raman Adiabatic Passage (SRIRAP) [11][12][13][14][15][16][17] are some of the important methods of the adiabatic population transfer of the quantum systems.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the amplitude, carrier frequency, and pulse duration, an important parameter is the frequency chirp of the pulse. In papers [2][3][4][5][6], the features of excitation of a two-level system by chirped laser pulses were investigated. In work [2], the dependence of the population of the upper level of the quantum system on the chirp was calculated numerically and analytically for various values of the pulse duration and field amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it was shown that in a certain range of parameters, the populations of a two-level system can be effectively controlled by variation of the chirp. In article [3], an effective scheme for controlling the superposition state of a two-level system using an ultrashort chirped laser pulse was proposed. In work [4], a high-precision population transfer was studied in a two-level model using a chirped Gaussian pulse.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, significant population transfer can be achieved using the chirped (or frequency-swept) pulse laser [28][29][30][31][32][33][34][35][36]37]. Raman Chirped Adiabatic Passage (RCAP) is another method of population transfer based on adiabatic passage [38,39].…”
Section: Introductionmentioning
confidence: 99%